(3MGTjI Ydi TQM GdJCSjSs - (3CHi GdaJM eMeO GdgGOi Hf CHi fUQ Hf GHi SYjO GdMSjfj GdYQGbi GdeOYh HJGL GdSYjOis; (3ehSi Hf eMeO GdTgjQ HbGVj RGOg GdQhejs
(3ChdgG (B:s
(3GdMeO ddg jbOQ ebGOjQ GdCTjGA HMceJg hHYO ajbhd gPg GdMhGTi eMQQI Ydi TQM GdCTcGd YOje GdeKGd dCSJGPi bGVi RGaQ GdQhei s
(3BNQgG (B:s
(3Cf jdbi c W Ydi W eKdkG Hd Edi W HMjK jchf c W eSGhjkG dM (B1 (3hfJe GdcdGe ai gPG GdebGe bGFdjf HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B105s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs